The automotive industry in times of economic crisis in years 2008−2009 - Nowak, Paweł (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2011)
This paper presents the complexity of the past two years in the Polish automotive industry and the impact and consequences of the economic downturn. The last two years were extremely challenging for the entire economy, especially the motor industry. The demand for cars decreased at the turn of 2008 and 2009. A dramatic plunge in sales has immediately taken a toll on suppliers and an entire economy. To prevent economic disaster, governments of many states allocated billions of euros and dollars to fund stimulating plans for buyers of the new vehicles. It was an aid which largely saved the sector from the decline. The additional aid packages for the entire economy and the financial sector managed to stabilize the disrupted economy.